Determinants of Managerial Values on Corporate Social Responsibility: Evidence from China - Zu, Liangrong (Journal of business ethics, 2009)
This article empirically investigates how Chinese executives and managers perceive and interpret corporate social responsibility (CSR), to what extent firms’ productive characteristics influence managers’ attitudes towards their CSR rating, and whether their values in favour of CSR are positively correlated to firms’ economic performance. Although a large proportion of respondents express a favourable view of CSR and a willingness to participate in socially responsible activities, we find that the true nature of their assertion is linked to entrepreneurs’ instincts of gaining economic benefits. It is the poorly performing firms, or rather, firms with vulnerable indicators – smaller in size, State-owned, producing traditional goods and located in poorer regions that are more likely to have managers who opt for a higher CSR rating. Managers’ personal characteristics per se are not significant in determining their CSR choice. Moreover, controlling for other observed variables, we find that managers’ CSR orientation is positively correlated with their firms’ performance. The better-off a firm is, the more likely its manager is to get involve in CSR activities. Firms with better economic performance before their restructuring would sustain higher post-restructuring performance.